Trabalho docente e qualidade da educação: dificuldades encontradas por professores dos anos iniciais do ensino fundamental - Blengini, Gabrielle Dellela (2015)
The aim of this study is to investigate the perception of elementary school teachers (initial grades) on the contributions of teaching practice to a quality education, aiming at comprehending the main difficulties they indentify in their work to build a quality education. This study was conducted in a city in the state of Sao Paulo with two municipal public elementary schools that scored highly in Prova Brasil (2011) regarding the city average. The methodology is characterized as qualitative. The data for this study was collected through socioeconomic survey questionnaires and semi-structured interviews conducted with eight teachers from both of the selected institutions. Critical approaches in education, innovation and quality education were adopted to address the research goal, contemplating the teacher as a fundamental agent in the transformation process of education. The results from the socioeconomic survey questionnaires and the interview with four teachers from each of the institutions selected for this study, named School A and School B, reveal the need for questioning the current processes of institutional assessment. This questioning is due to the fact that most of the pedagogues, participants of this study, highlight more negative aspects rather than contributions of the external evaluations for quality teaching practice. The teachers believe that the school in which they work promotes quality education, but the participants demonstrate different understanding about the quality of education that draws attention to the polysemy of the concept. They understand that changes in teaching practice (innovations) should be part of the monthly curriculum plan and of the teaching/learning processes. The participants point out that the difficulties of teaching practice are mainly found in pedagogical practice, in the lack of physical and material aspects in the schools, in the working conditions, with emphasis on low pay that teachers from basic education receive, in the lack of family support for students, in the devaluation of education and teaching staff, and student indiscipline. They noted that their training, obtained through the public high school teacher training, their undergraduate studies, their continuing education, and graduate course is what contributes to their pedagogical practice. It is also stated that most of them follow theoretical conceptions based on active teaching methodologies, although the data supports the multidimensional components of their conception of quality and theoretical principles. This survey may provide some elements that contribute to the reflection at the university about the educator’s professional performance, aiming at the quality of the teaching/learning process and it may contribute to the enhancement of public schools teachers’ efforts.